1963
DOI: 10.2134/agronj1963.00021962005500010004x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compaction on Physical Properties of Sand‐Soil‐Peat Mixtures at Various Moisture Contents1

Abstract: Synopsis Eight soils in sand‐soil‐peat mixtures reacted differently to compaction as reflected in percolation rates and aeration porosity. Generally, if the mixtures contained 50% or less total sand, compaction at high moisture contents resulted in inadequate percolation rates. Mixtures containing 70% total sand maintained adequate percolation rates under compaction but the average available moisture content of such mixtures was only 1.2 inches per foot of depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
4
7
0
Order By: Relevance
“…These results suggest that suitable sand contents for a high-quality, general-use soil using either soil material should be about 65%. This conclusion corresponds with that of Swartz and Kardos (1963), who recommended that total sand content of a soil mixture should approach 70% by weight. This conclusion also conforms with that of Waddington et al (1974), who noted that 50 to 60% of a coarse amendment was required to effectively modify a silt loam soil.…”
Section: Analysis Of Turf Clipping Yieldsupporting
confidence: 88%
“…These results suggest that suitable sand contents for a high-quality, general-use soil using either soil material should be about 65%. This conclusion corresponds with that of Swartz and Kardos (1963), who recommended that total sand content of a soil mixture should approach 70% by weight. This conclusion also conforms with that of Waddington et al (1974), who noted that 50 to 60% of a coarse amendment was required to effectively modify a silt loam soil.…”
Section: Analysis Of Turf Clipping Yieldsupporting
confidence: 88%
“…Although trampling did not significantly affect total porosity or bulk density (Table 3), intensive foot traffic and wear tore the cells of turfgrasses, and apparently closed macropores of thatchy soil surface. The results of soil volume and mass relationships indicate that the putting green mixture of sand and peat restricted soil compaction, thus agreeing with Swartz and Kardos (1963) or Brown and Duble (1975). Soil compaction was, although slightly, recorded by increased soil mechanical impedance (Fig.…”
Section: Soil Physical Conditionsupporting
confidence: 66%
“…Both Howard 3 and Kunze 4 found in plot experiments that a mixture of 70 to 85% sand, 10% peat moss, and 5% to 20% soil were most resistaqt to compaction. A laboratory investigation on soil mixtures without a grass cover by Swartz and Kardos (1963) revealed that mixtures with greater than 70% sand were required to provide adequate percolation rates after compaction. No study is available, however, which reports more than one or two of the physical characteristics of a range of mixtures.…”
Section: ----------•----------mentioning
confidence: 99%